THE APPLICATION OF THE MAKE A MATCH TYPE COOPERATIVE LEARNING MODEL TO BIOLOGY LEARNING OUTCOMES IN ECOSYSTEM MATERIAL FOR CLASS X- IPA AT SMA NEGERI 1 RINDI UMALULU - Anita Teul Kawutak; Yohana Makaborang; Yohana Ndjoeroemana (JURNAL EDUSCIENCE, 2023)
The research with the of knowing student learning outcomes using the Make A Match type cooperative learning model on ecosystem material at SMA Negeri 1 Rindi Umalulu. This research is a Cassroom Action Research (PTK) consisting of pre-cycle activities, cycle 1 and cycle 2, with a total of 30 students. Pre-cycle activities, it was found that overall student learning outcomes with an average of 53.2, the number of students who completed 2 people with a percentage of 6.6% and who did not complete 28 people with a percentage of 93.3%. In cycle 1, student activities consisting of affective aspects included 9 students with good predicates and 21 students with sufficient predicates. Then the learning outcomes in cycle 1 mean the average value of all students is 65.4 students who complete consisting of 14 people with a percentage of 46.6% who do not complete consisting of 16 people with a percentage of 53.3%. In the cycle there were 16 students with very good predicates and 14 students with good predicates. The results of learning in cycle 2, the average value of all students is 76.5 students who complete consist of 25 people with a percentage of 83.3% and students who do not complete consist of 5 people with a percentage of 16.6%. The application of the Make A Match cooperative learning model to class X Biology learning outcomes in class X-IPA ecosystem material at SMA Negeri 1 Rindi Umalulu has increased.Keywords: Make A Match, (Cooperative) Learning Model, Learning Outcomes. ABSTRAKPenelitian dilakukan untuk mengetahui hasil belajar siswa dengan menggunakan model pembelajaran kooperatif tipe Make A Match pada materi ekosistem di SMA Negeri 1 Rindi Umalulu. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang terdiri dari kegiatan prasiklus, siklus 1 dan siklus 2, dengan jumlah siswa sebanyak 30 orang. Kegiatan pra siklus di temukan hasil belajar siswa secara keseluruhan dengan rata- rata 53,2, jumlah siswa yang tuntas 2 orang dengan presentase 6,6% dan yang tidak tuntas 28 orang dengan presentase 93,3%. Pada siklus 1, kegiatan siswa yang terdiri dari aspek afektif meliputi 9 siswa dengan predikat baik dan 21 siswa dengan predikat cukup. Kemudian hasil belajar pada siklus 1 nilai rata- rata seluruh siswa 65,4 siswa yang tuntas terdiri dari 14 orang dengan presentase 46,6% yang tidak tuntas terdiri dari 16 orang dengan presentase 53,3%. Pada siklus 2 terdapat 16 siswa dengan predikat sangat baik dan 14 siswa dengan predikat baik. Hasil pembelajaran pada siklus 2, nilai rata- rata seluruh siswa adalah 76,5, siswa yang tuntas terdiri dari 25 orang dengan presentase 83,3% dan siswa yang tidak tuntas terdiri dari 5 orang dengan presentase 16,6%. Penerapan model pembelajaran kooperatif tipe Make A Match terhadap hasil belajar Biologi pada materi ekosistem kelas X- IPA di SMA Negeri 1 Rindi Umalulu meningkat.Kata kunci: Make A Match, Model Pembelajaran(kooperatif), Hasil Belajar.